Effect of cross-sections data on calculated static neutronic parameters of PWR MOX/UO2 core transient benchmark case using NODAL3 code - Luthfi, Wahid; Pinem, Surian (Acta Polytechnica, 2023)
This paper describes the effect of cross-section data generated by several codes on calculated neutronic parameters. The Pressurized Water Reactor Mixed Oxide and Uranium Oxide (PWR MOX/UO2) Core Transient Benchmark case was chosen because it has been used widely to validate neutronic codes. The cross-section data in this study will be generated by SRAC, Serpent, and HELIOS codes. The NODAL3 code will be used to calculate neutronic parameters from each cross-section. The neutronic parameters calculated by NODAL3 are the effective multiplication factor (keff), control rod worth, critical boron concentration, and power distribution under Hot Zero Power (HZP) conditions. The Power-Weighted Error (PWE) and Error-Weighted Error (EWE), as a measure of the relative error in fuel assembly power, are less than 5 %, indicating that the calculation is consistent with DeCART as a reference. The difference in calculated radial power peaking factor for all three cross-sections to reference data reaches 6.284 % (G-3), 8.438 % (G-3), and 10.998 % (C-7), respectively, for SRAC, Serpent, and HELIOS. The axial power distribution calculated by NODAL3 at the top and bottom of the reactor core has a relative error that peaked at 16.60 %, 13.86 %, and 10.20 %, respectively, for cross-sections provided by SRAC, Serpent, and HELIOS. Further improvements are needed for NODAL3 by applying various discontinuity factors to improve its performance.